(untitled) (Journal of Rashid Latif Medical College, 2025)
Background: Fear of failure (FoF) is a psychological construct that can affect academic performance and mental health in students. Objectives: This study aimed to assess the level of FoF among medical students at the University Institute of Physiotherapy (UIPT), compare FoF across genders, academic years, GPA categories, and interest in studying medicine. Objective To assess the prevalence and severity of fear of failure (FoF) among medical students at the UIPT, Lahore during the academic year 2024, and to examine its association with gender, academic year, grade point average (GPA), and students’ interest in studying medicine. Methodology: A cross-sectional study was conducted among 420 undergraduate medical students from 2nd to 5th year during the academic year 2024. Participants completed the Performance Failure Appraisal Inventory (PFAI). Data were analyzed using SPSS 26.0, applying Mann-Whitney U-test and Kruskal-Wallis test to compare domain scores across groups. Cronbach’s α was calculated for reliability. Results: The overall mean FoF score was −0.28, indicating a relatively low level of FoF. Female students showed significantly higher fear of devaluing self-estimate, while males had higher fear of important others losing interest. Third-year students exhibited higher levels of FoF than other years. Students with GPA <3.5 and >4.9 reported the highest FoF. Reliability analysis showed excellent internal consistency (Cronbach’s α = 0.92). Conclusion: Although overall FoF was low, significant differences were observed across gender, GPA, and year of study. Targeted counseling is recommended, especially for high- and low-GPA students and those transitioning to clinical years.